ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL GEOMETRI BERDASARKAN TAHAPAN KASTOLAN DI KELAS VIII SMP NEGERI 7 SIJUNJUNG - JUFRI . (Jurnal Edukasi dan Penelitian Matematika, 2020)
Analysis of student’s errors is an important thing to do to determine the mastery of student material. In fact, it was found that there were mistakes made by students of class VIII  SMP N 7 Sijunjung in solving math problems with cubes and blocks. Based on the results of the study showed that students made a lot of mistakes including: 1) conceptual errors, that is students could not choose or apply the volume formula of cubes and beams, students were wrong in determining the formula for beam surface area and students did not write the formula for wall-shaped beam surface area, 2) procedural errors, that is students make mistakes in determining the steps in solving problems and students do not solve problems until the final results, 3) technical errors, that is students make mistakes in determining the value of arithmetic operations and wrong use of the math operations. The percentage of errors in class VIII-3 students of SMP N 7 Sijunjung in solving geometry problems of cube and block material was 60.34% with the biggest error being procedural error by 34.29% and the smallest error was tecnichal error by 2.86%. Keywords—Analysis of student’s errors, conceptual errors, procedural errors, technical errors, geometry.